Pengaruh Product Browsing terhadap Pembelian Impulsif pada Produk Fashion di Ecommerce Shopee dengan Flash Sale sebagai Variabel Moderasi dalam Persepektif Bisnis Islam - Fatih Fuadi; Heni Verawati; Lita Aryani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
In the rapidly growing era of digitalization, significant changes have occurred in consumer behavior, especially with the existence of e-commerce platforms and online marketing innovations. Today's consumers frequently browse for information about fashion products before making a purchase. Goals of the study to examine the impact of product searches on impulsive buys, Together with the relationship's moderating effect of flash sales, as well as sharia business perspective. Purposive sampling is a quantitative research method that is utilized. involving Shopee users in Bandar Lampung City. Data were collected using a Google Form-based questionnaire with a Likert scale. The findings indicated that the chance of making an impulsive purchase increased with the amount of time spent searching.. In addition, flash sales were shown to moderate this relationship, increasing impulse buying tendencies when found during browsing. These findings imply that the management of product browsing and flash sale offers needs to be considered in marketing strategies, taking into account the Shariah perspective to ensure fair and non-wasteful transactions.